Method for modifying aramid fibers
Surface modification of aramid fibers using acid treatment, microwave irradiation, and mechanical bending, combined with coupling agents, addresses the adhesion issues with elastomeric materials, improving mechanical properties and expanding application in tires and belts.
Patent Information
- Application Number
- JP2023075973
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-03-31
- Filing Date
- 2023-05-02
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2036-08-18
AI Technical Summary
Aramid fibers, such as Kevlar, exhibit poor adhesion to elastomeric materials due to their high crystallinity and smooth surface, leading to poor material performance and limited applications.
Surface modification of aramid fibers through acid treatment, microwave irradiation, mechanical bending, and coupling agents to increase surface roughness and adhesion, including methods like soaking in acid solutions, microwave exposure, and mechanical deformation combined with coupling agent application.
Improves the adhesion of aramid fibers to elastomeric materials, enhancing the mechanical properties and expanding their application in products like tires and belts.
Smart Images

Figure 0007615517000004 
Figure 0007615517000005 
Figure 0007615517000006
Abstract
Description
[Technical field]
[0001] This application claims priority to U.S. Provisional Patent Application No. 62 / 206,611, filed August 18, 2015, and U.S. Provisional Patent Application No. 62 / 316,000, filed March 31, 2016, the entire contents of which are incorporated herein by reference. The present disclosure relates to a method for modifying aramid fiber surfaces to improve roughness and adhesion to elastomeric materials, such as rubber-containing compositions. The present disclosure further relates to the use of surface-modified aramid fibers in producing vulcanized products, such as tires and belts. [Background technology]
[0002] Fibers are commonly used as reinforcing members to increase the strength and durability of various elastomeric materials and related products, such as rubber tires or belts. Aramid fibers, such as Kevlar fibers, can exhibit poor adhesion to elastomers due to their high crystallinity and smooth outer surface. The surface of the fiber can also be chemically inert, further reducing adhesion to other materials. Lack of sufficient adhesion at the interface with the elastomer and reinforcing matrix often results in poor material performance and can limit the potential applications of the elastomeric material.
[0003] Attempts have been made to modify and treat the surface of fibers to improve adhesion to elastomeric materials. For example, plasma treatment can increase rubber adhesion by increasing the activation energy at the fiber surface or by etching the fiber surface to increase its roughness. Other methods to increase adhesion include the use of coatings or adhesives. Coatings or adhesives are typically applied to aramid cords to create an outer surface that is more compatible with the material that encases the fiber. Adhesive systems can involve multiple steps and require the introduction of new materials into the rubber product or fiber, both of which can increase the time and cost associated with manufacturing the product. Summary of the Invention [Problem to be solved by the invention]
[0004] It is an object of the present disclosure to alleviate or overcome one or more of the problems associated with the prior art. It has been discovered that treatment of aramid fibers with acid, microwave, mechanical bending, contact with coupling agents, and combinations thereof, can beneficially modify the aramid fiber surface and enhance adhesion of the fiber surface to elastomeric materials. [Means for solving the problem]
[0005] A first aspect is a method for modifying an aramid fiber surface, the method including: (a) contacting aramid fibers with an acid solution for a period of time to form pretreated aramid fibers, (b) removing the aramid fibers of step (a) from the acid solution and immersing the pretreated aramid fibers in a liquid, (c) irradiating the pretreated aramid fibers in the liquid to modify the aramid fiber surface, and (d) removing the aramid fibers from the liquid.
[0006] In one example of embodiment 1, the aramid fiber is poly(paraphenylene terephthalamide).
[0007] In another example of embodiment 1, the aramid fiber is poly(metaphenylene isophthalamide).
[0008] In another example of aspect 1, the acid is selected from the group consisting of hydrochloric acid, nitric acid, sulfuric acid, hydrobromic acid, phosphoric acid, hydroiodic acid, perchloric acid, and combinations thereof.
[0009] In another example of embodiment 1, the aramid fibers are immersed in an acid solution, for example, for at least 20 minutes.
[0010] In another example of embodiment 1, the liquid in step (b) is water, for example, deionized water (DI water).
[0011] In another example of embodiment 1, the irradiating step (c) is carried out in a vessel, for example, in a microwave, which exposes the fibers to microwave energy.
[0012] In another example of embodiment 1, step (c) includes irradiating the pretreated aramid fibers for at least 15 seconds.
[0013] In another example of embodiment 1, step (c) comprises irradiating the pretreated aramid fibers at a power level of at least 60 watts.
[0014] Another example of embodiment 1 is an aramid fiber prepared by the method of claim 1 having improved adhesion to elastomers.
[0015] In the first aspect, any one or more of the examples of the first aspect described above may be provided, either alone or in combination.
[0016] In a second embodiment, the aramid fibers of embodiment 1, such as the aramid fibers of step (d), are contacted with a coupling agent.
[0017] In embodiment 2, the coupling agent is a vinyl substituted compound, for example, a cyclic compound having two or more vinyl groups or a cyclic compound having branched alkyl substituents.
[0018] In another example of embodiment 2, the coupling agent is a vinyl substituted silicone, e.g., a molecular weight (M w ) is a low molecular weight silicone.
[0019] In another example of embodiment 2, the coupling agent is mixed with a solvent, such as an organic solvent or supercritical carbon dioxide.
[0020] In another example of embodiment 2, the aramid fibers of step (c) are immersed in the coupling agent fluid for at least 30 minutes.
[0021] In another example of Embodiment 2, the aramid fiber has an adhesion to the rubber composition of greater than 0.8 MPa per Test #1.
[0022] In the second aspect, any one or more of the examples of the first or second aspects described above may be provided, either alone or in combination.
[0023] A third embodiment is an aramid fiber having improved adhesion to an elastomeric material, prepared by immersing the aramid fiber in a liquid and irradiating the aramid fiber to modify its surface.
[0024] In embodiment 3, the aramid fiber surface is modified by the formation of blisters on the surface, the blisters extending outwardly from the surface of the aramid fiber as compared to the blister-free aramid fiber surface prior to the irradiation step.
[0025] In another example of embodiment 3, the aramid fiber is poly(paraphenylene terephthalamide) or poly(metaphenylene isophthalamide).
[0026] In another example of embodiment 3, the aramid fibers are irradiated in a microwave vessel for at least 30 seconds with a power of at least 60 watts.
[0027] In the third aspect, any one or more of the examples of the third aspect described above may be provided, either alone or in combination.
[0028] A fourth aspect is a method of modifying an aramid fiber surface, the method including (a) applying tension to the aramid fiber, (b) bending the aramid fiber at an angle greater than 30°, and (c) releasing the tension on the aramid fiber.
[0029] In an example of embodiment 4, the aramid fiber is poly(paraphenylene terephthalamide) or poly(metaphenylene isophthalamide).
[0030] In another example of embodiment 4, the tension applied to the aramid fibers in step (a) is at least 0.5 N.
[0031] In another example of embodiment 4, step (b) includes bending the aramid fibers at an angle ranging from 45 to 150 degrees.
[0032] Another example of the fourth embodiment includes bending the aramid fibers at an angle of at least 30 degrees two or more times.
[0033] In another example of embodiment 4, step (b) includes bending the aramid fibers at an angle of at least 90 degrees two or more times.
[0034] In another example of embodiment 4, step (b) is carried out in a continuous process by passing the aramid fibers over a member and applying bending to the aramid fibers.
[0035] In another example of embodiment 4, the member is a roller or a static cylinder having a curved surface.
[0036] In another example of embodiment 4, the aramid fibers are twisted after step (c) at a twist rate in the range of 10 to 200 turns / meter.
[0037] In the fourth aspect, any one or more of the examples of the fourth aspect described above may be provided, either alone or in combination.
[0038] In a fifth embodiment, the aramid fibers of embodiment 4, such as the aramid fibers of step (c), are contacted with a coupling agent.
[0039] In embodiment 5, the coupling agent is a vinyl substituted compound, for example, a cyclic compound having two or more vinyl groups or a cyclic compound having branched alkyl substituents.
[0040] In another example of embodiment 5, the coupling agent is a vinyl substituted silicone compound, e.g., a compound having a molecular weight (M w) is a low molecular weight silicone.
[0041] In another example of embodiment 5, the coupling agent is mixed with a solvent, such as an organic solvent or supercritical carbon dioxide.
[0042] In another example of embodiment 5, the aramid fibers of step (c) are immersed in the coupling agent fluid for at least 30 minutes.
[0043] In another example of Embodiment 5, the aramid fiber has an adhesion to the rubber composition of greater than 0.8 MPa per Test #1.
[0044] In the fifth aspect, any one or more of the examples of the fourth or fifth aspects described above may be provided, either alone or in combination.
[0045] A sixth embodiment is an aramid fiber having improved adhesion to an elastomeric material, the aramid fiber being prepared by bending the aramid fiber at an angle greater than 30° while a tension is applied to the aramid fiber.
[0046] In an example of the sixth embodiment, the aramid fibers are poly(paraphenylene terephthalamide) or poly(metaphenylene isophthalamide).
[0047] A seventh aspect is a method of improving adhesion of aramid fibers to an elastomeric material, the method including (a) contacting aramid fibers with a coupling agent fluid, (b) removing the aramid fibers from the fluid, and (c) drying the aramid fibers.
[0048] In an example of the seventh embodiment, the aramid fibers are poly(paraphenylene terephthalamide) or poly(metaphenylene isophthalamide).
[0049] In another example of the seventh embodiment, the coupling agent is a vinyl substituted compound, for example, a cyclic compound having two or more vinyl groups or a cyclic compound having branched alkyl substituents.
[0050] In another example of the seventh embodiment, the coupling agent is a vinyl substituted silicone, e.g., a tert-butyl ether ester having a molecular weight (M w ) is a low molecular weight silicone.
[0051] In another example of the seventh embodiment, the coupling agent fluid in step (a) is a coupling agent mixed with a solvent, such as an organic solvent or supercritical carbon dioxide.
[0052] In another example of the seventh embodiment, the aramid fibers have an adhesion to the rubber composition of greater than 0.8 MPa per Test #1.
[0053] In another example of the seventh embodiment, the aramid fibers are contacted with an acid solution prior to step (a).
[0054] In another example of the seventh embodiment, the aramid fibers are irradiated in the liquid prior to step (a).
[0055] In another example of the seventh embodiment, prior to step (a), the aramid fibers are bent at an angle greater than 30° while a constant tension is applied to the aramid fibers.
[0056] In the seventh aspect, any one or more of the examples of the seventh aspect described above may be provided alone or in combination.
[0057] An eighth embodiment is an aramid fiber having improved adhesion to an elastomeric material, the aramid fiber being prepared by contacting the aramid fiber with a coupling agent fluid for at least 30 minutes.
[0058] In an example of the eighth embodiment, the aramid fibers are poly(paraphenylene terephthalamide) or poly(metaphenylene isophthalamide).
[0059] In another example of the eighth embodiment, the coupling agent is a vinyl substituted compound (e.g., a cyclic compound having two or more vinyl groups) or a cyclic compound having a branched alkyl substituent or a vinyl substituted silicone (e.g., a molecular weight (M) of less than 1000). w ) or a combination thereof.
[0060] The accompanying drawings are included to provide a further understanding of the principles of the invention and are incorporated in and constitute a part of this specification. The drawings illustrate one or more embodiment(s) and, together with the description, serve to explain the invention, its principles and operation. It should be understood that the various features disclosed in this specification and the drawings can be used in any combination. As a non-limiting example, the various features can be combined with each other as described in the specification as aspects. [Brief description of the drawings]
[0061] The above and other features, aspects, and advantages will be better understood by reading the following detailed description in conjunction with the accompanying drawings.
[0062] [Figure 1] 1 is a scanning electron microscope image of untreated poly(paraphenylene terephthalamide) fibers. [Diagram 2] 1 is a scanning electron microscope image of poly(paraphenylene terephthalamide) fibers immersed in a sulfuric acid solution. [Diagram 3] 1 is a scanning electron microscope image of poly(paraphenylene terephthalamide) fibers immersed in a sulfuric acid solution and subsequently irradiated with microwave energy. [Figure 4] 1 is a scanning electron microscope image of poly(paraphenylene terephthalamide) fibers immersed in a sulfuric acid solution and subsequently irradiated with microwave energy. [Diagram 5] It is a mechanical processing device used to apply uniform and uniform compressive and bending strain to poly(paraphenylene terephthalamide) fibers. [Figure 6] 7 is an optical microscope image of a poly(paraphenylene terephthalamide) fiber passed through the device shown in FIG. 6. [Figure 7] 1 is a schematic of a sample preparation method for adhesion testing to measure adhesion of fibers to elastomeric materials. [Figure 8] 1 is a schematic of the shear lag model for adhesion testing to measure adhesion of fibers to elastomeric materials. [Figure 9] 1 is a graph showing the measured adhesion of aramid fibers to rubber compositions according to Test #1. [Figure 10] 1 is a graph showing the measured adhesion of aramid fibers to rubber compositions according to Test #1. [Figure 11] 1 is a graph showing the measured adhesion of aramid fibers to rubber compositions according to Test #1. [Figure 12] 1 is a graph showing the measured adhesion of aramid fibers to rubber compositions according to Test #1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0063] The terminology used herein is for the purpose of describing the embodiments only and is not to be construed as limiting the invention as a whole.
[0064] As used herein, when a range is given, such as 5-25 (or 5 to 25), this preferably means at least 5 or more, and further separately and independently preferably not more than 25 or less than 25. In certain instances, such ranges independently define at least 5, and further separately and independently define not more than 25.
[0065] As used herein, the term "phr" means parts by weight of rubber. If the rubber composition contains two or more rubbers, "phr" means parts by weight per 100 parts of all rubbers combined.
[0066] The present disclosure relates to the adhesion of aramid fibers to rubber or vulcanizable compositions typically used to manufacture elastomeric compositions, such as tires or belts. The aramid fibers can be in the form of reinforcing members, such as threads, filaments, fibers, cords, fabrics, or combinations thereof. One example of an aramid fiber is Kevlar®, a highly crystalline material with excellent tensile properties due to hydrogen bonds between molecular chains. The preparation method for these fibers results in a highly anisotropic structure, in which lamellae spread radially outward from the center. Due to the high crystallinity, the fiber surface is very smooth. It has been found that it is possible to open up the interior portion of the aramid fiber, exposing the amorphous portion, and to insert or infiltrate the fiber with agents that bond with elastomeric materials, resulting in better adhesion and improving the overall mechanical properties of elastomeric products in which one or more aramid fibers are maintained.
[0067] Aramid fibers can be treated to expose the subsurface portions of the fibers. Aramid fibers can have microvoids that can be mass-incorporated. These voids can be the subject of the introduction of adhesion promoters, such as coupling agents. This disclosure describes treatments that impart roughness to the aramid fiber surface and / or open the voids and make them more accessible. After treating the fiber surface and improving the adhesion of the fibers to elastomeric materials, the introduction of coupling agents or crosslinking monomers into the open interior portions of the fibers can be performed.
[0068] As described herein, aramid fibers are polymeric fibers consisting partially, predominantly, or exclusively of aromatic rings linked by amide bridges, or optionally additionally by other bridge structures. The structure of such aramids is defined by the general formula of the repeating unit: (-NH-A1-NH-CO-A2-CO-) n
[0069] In the formula, A1 and A2 are the same or different aromatic and / or polyaromatic and / or aromatic heterocycles, which may be substituted. For example, the amide (-CO-NH-) bond is directly bonded to two aromatic rings. In one embodiment, at least 85% of the amide (-CONH-) bond is directly bonded to two aromatic rings. A1 and A2 can each be independently selected from 1,4-phenylene, 1,3-phenylene, 1,2-phenylene, 4,4'-biphenylene, 2,6-naphthylene, 1,5-naphthylene, 1,4-naphthylene, phenoxyphenyl-4,4'-diylene, phenoxyphenyl-3,4'-diylene, 2,5-pyridylene and 2,6-quinolylene, which may or may not be substituted by one or more substituents. Substituents include halogen, C1-C4 alkyl, phenyl, carboalkoxy, C1-C4 alkoxy, acyloxy, nitro, dialkylamino, thioalkyl, carboxyl and sulfonyl. The (-CO-NH-) group may also be substituted by a carbonyl-hydrazide (-CONHNH-) group, an azo or an azoxy group.
[0070] Additives can be used with the aramids, for example up to about 10% by weight of other polymeric materials can be blended with the aramids, or copolymers can be used having as much as 10% of other diamines substituting for the diamine of the aramid or as much as 10% of other diacid chlorides substituting for the diacid chloride of the aramid.
[0071] Suitable aramid fibers are described in Man-Made Fibers--Science and Technology (Volume 2, Section titled Fiber-Forming Aromatic Polyamides, page 297, W. Black et al., Interscience Publishers, 1968). M-aramids are aramids in which the amide bonds are meta to each other, and p-aramids are aramids in which the amide bonds are para to each other. In the practice of this disclosure, the aramids most often used are poly(paraphenylene terephthalamide) (e.g., Kevlar®) and poly(metaphenylene isophthalamide) (e.g., Nomex®).
[0072] The method for modifying the surface of aramid fibers can include contacting the aramid fibers with an acid, for example, an acid solution, as an acid treatment. The acid can be any suitable acid. For example, inorganic or strong acids can be used to treat the aramid fibers. The acid can include, for example, hydrochloric acid (HCl), nitric acid (HNO3), sulfuric acid (H2SO4), hydrobromic acid (HBr), hydroiodic acid (HI), perchloric acid (HClO4, HClO3), or any combination thereof. Other acids can include phosphoric acid, chromic acid, carbonic acid, ascorbic acid, acetic acid, citric acid, fumaric acid, maleic acid, tartaric acid, succinic acid, glycolic acid, or any combination thereof.
[0073] The acid can be in solution, for example, an aqueous solution. The acid solution can have any suitable concentration of acid, for example, the acid can be present in the solution at a concentration ranging from 1-99% by weight, 5-90, 10-80, 15-60, or 20-50, or at 25, 30, 35, 40, or 45% by weight.
[0074] The aramid fibers can be contacted with the acid by any conventional method. For example, the fibers can be immersed or soaked in an acid solution for a per-determined period of time. The fibers can be contacted with the acid for a period ranging from 20 minutes to 2 days, 30 minutes to 24 hours, 45 minutes to 12 hours, or for 1 hour, 2 hours, 4 hours, or 6 hours. The fibers can be contacted with the acid at any suitable temperature, for example, at a temperature ranging from 20 to 140°C, 25 to 100°C, or at 30, 40, 50, 60, 70, 80, or 90°C.
[0075] The acid treatment of the aramid fibers can be carried out as a separate treatment method prior to bonding the fibers to the elastomeric material, or the acid treatment can be combined with additional treatments applied to the fibers, for example, prior to bonding to the elastomer.
[0076] In another method of modifying the aramid fiber surface, the fibers may be irradiated, for example, by exposing the fibers to microwaves or microwave energy. Microwave irradiation of the fibers may be performed at any frequency in the microwave range, for example, from 300 MHz to 300 GHz. In one embodiment, a microwave oven (e.g., an oven) may be used to irradiate the aramid fibers. The microwave oven may irradiate the fibers at frequencies ranging from 1 to 4 GHz, 2 to 3 GHz, or at 2.4, 2.45, or 2.5 GHz. The microwave oven may be operated at any suitable power, for example, at least 60 watts. The power level of the microwave oven may be in the range of 60 watts to 2.5 kilowatts, 75 watts to 1 kilowatt, 100 to 500 watts, or 150 to 250 watts.
[0077] The process can be carried out continuously using a commercial microwave system with a conveyor. The process can also be carried out using a closed microwave system in a batch type processing system. The fibers can be irradiated for any suitable time. For example, aramid fibers can be irradiated for a period ranging from 15 seconds to 10 minutes, 30 seconds to 5 minutes, 45 seconds to 3 minutes, or for 1 minute or 2 minutes.
[0078] Irradiation of the aramid fibers can cause evaporation of liquids below the fiber surface. The liquid in the fiber may be present in the fiber after the fiber is produced (e.g., residual solvent) or may be introduced by contacting the fiber with a permeate, such as an acid solution or a solvent, alone or with one or more substances. Gas or vapor generated within the fiber during irradiation tends to migrate toward the fiber surface and escape. Exposing the fiber to irradiation energy, such as microwave energy, can cause blisters to form on the fiber surface. Blisters on the surface of aramid fibers exposed to microwave energy can be seen in FIG. 4. The blisters radiate outward from the fiber surface, imparting roughness to the fiber surface and improving adhesion of other materials. As shown, the blisters are raised on the surface of the fiber compared to the smooth, blister-free aramid fiber surface before irradiation (e.g., as shown in FIG. 1). The blisters on the aramid fiber surface can provide a textured surface for the elastomeric material to adhere to, and the blisters can further form a surface that traps the material on the fiber surface and improves adhesion. In one example, when the aramid fiber comes into contact with the elastomeric material, the blisters can burst and open, allowing the material to fill the exposed voids created by the open blisters both on and below the surface of the fiber. As a result, the material can fill the voids within the fiber and along the textured surface created by the blisters.
[0079] Preferably, the aramid fibers are immersed in a liquid before irradiation. Any suitable liquid can be used, such as water (e.g., deionized water). If heated for a long period of time, the aramid fibers can decompose or be damaged. Immersing the fibers in a liquid during irradiation can prevent the fibers from scorching or carbonizing. The liquid can act as a heat sink, minimizing the temperature rise during irradiation. The container for irradiating the aramid fibers, such as a microwave oven, can be equipped with a temperature sensor. One or more temperature sensors can control the amount of radiant energy the fibers are exposed to during processing and prevent the fibers from being exposed to high temperatures that could damage them.
[0080] In one embodiment, the aramid fibers can be contacted with an acid solution to form a pretreated fiber. The fibers can be removed from the acid solution and immersed in another liquid, such as water, before being irradiated with microwave energy to further treat the aramid fibers. After removal from the acid solution, the fibers can be optionally dried.
[0081] Another method of modifying the aramid fiber surface is to mechanically treat the fibers. A constant tension or load can be applied to the aramid fibers. For example, the fibers can be placed in a tensile tester to apply a constant tensile load. The tension applied to the fiber can be in the range of 0.25 Newtons (N) to 10 N, 0.5 to 5 N, 0.75 to 3 N, or 1 or 2 N. Under constant tension, a compressive and bending strain can be applied to the fiber. The compressive and bending strain can be applied in a continuous process by passing the fiber under tension over a member that places the fiber at a bending angle, for example, in the range of 30 to 150°, 45 to 140°, 60 to 130°, or at a bending angle of 70, 80, 90, 100, 110, or 120°.
[0082] The aramid fiber can be bent at one or more points during mechanical processing, for example, the fiber can be bent 2 to 20 times. Each bend in the fiber can be at the same or different angle. In one embodiment, the fiber can be bent at least two times with a bend angle of at least 90, 100, 110, or 120°. An example of a bending device configuration is shown in FIG. 5. As shown, the aramid fiber has six consecutive bends, four of which are 120°.
[0083] Compressive and bending strains can be applied to the aramid fibers by passing the fibers over a member that changes the path of the fibers to a desired bend angle. For example, the member can have a curvature, such as a curved roller or a static cylinder. A series of members can be arranged to pass the fibers through or along an array of bending members to impart one or more bends at any desired angle.
[0084] The above treatments, acids, irradiation, and mechanical manipulations modify the aramid fiber surface. The fiber surface may be altered to expose the inner material of the fiber that is beneath the outer surface. Before or after the above treatments, coupling agents may be introduced into the fiber to promote adhesion to elastomeric materials.
[0085] The aramid fibers may be contacted with one or more coupling agents. For example, the coupling agent may be liquid at room temperature or may be heated to its melting point so that the fibers can be immersed in the coupling agent for a period of time. The fibers may be contacted with the coupling agent for a period ranging from 20 minutes to 2 days, 30 minutes to 24 hours, 45 minutes to 12 hours, or 1 hour, 2 hours, 4 hours, or 6 hours. The fibers may be contacted with the coupling agent at any suitable temperature, for example, at a temperature ranging from 20 to 140, 25 to 100, or at 30, 40, 50, 60, 70, 80, or 90°C.
[0086] The coupling agent may be combined with another fluid, such as a solvent, prior to contacting the fibers. The coupling agent may be present in the solvent or solvent system at any suitable concentration, such as 10-90% by weight.
[0087] The solvent may be an organic solvent. As discussed below, various organic solvents may be used in the organic solvent system. Suitable general solvent classes include, but are not limited to, C1-C6 alcohols, halogenated hydrocarbons, saturated hydrocarbons, aromatic hydrocarbons, ketones, ethers, alcohol ethers, nitrogen-containing heterocycles, oxygen-containing heterocycles, esters, amides, sulfoxides, carbonates, aldehydes, carboxylic acids, nitrites, nitrated hydrocarbons, and acetamides.
[0088] An organic solvent may be included in the solvent system, which may be a single solvent or a mixture of solvents. Generally, the solvent mixture includes at least two solvents, and may further include 5 to 10 solvents. Solvents include, but are not limited to, perchloroethylene, isooctane (also called trimethylpentane), hexane, acetone, methylene chloride, toluene, methanol, chloroform, ethanol, tetrahydrofuran, acetonitrile, methyl ethyl ketone, pentane, N-methylpyrrolidone, cyclohexane, dimethylformamide, xylene, ethyl acetate, chlorobenzene, methoxyethanol, morpholine, pyridine, piperidine, dimethyl sulfoxide, ethoxyethanol, isopropanol, propylene carbonate, petroleum ether, diethyl ether, dioxane, and mixtures thereof.
[0089] In one embodiment, the solvent can be supercritical carbon dioxide. Carbon dioxide is desirable due to its ready availability, non-flammability, and environmental safety (non-hazardous). The critical temperature of carbon dioxide is 31° C., and a dense (or compressed) gas phase above the critical temperature and close to (or exceeding) the critical pressure is often referred to as a “supercritical fluid”. In this state, carbon dioxide is dense as a fluid, but also fills containers like a gas. Supercritical carbon dioxide is an effective solvent for small molecules and a poor solvent for polymers, with the exception of some fluoropolymers and silicones. Thus, the density and solvent properties of supercritical carbon dioxide are used to transport small molecules into the microvoids close to the surface of the aramid fibers, where they can act as a coupling agent to bind and help crosslink the matrix (e.g., elastomeric materials or rubbers).
[0090] In one embodiment, coupling agents useful for improving adhesion between fibers and elastomeric materials can include vinyl-substituted compounds having two, three, four or more vinyl substituents or groups. Vinyl-substituted compounds can include, for example, linear or cyclic compounds having two or more vinyl groups. Cyclic compounds can include C3-C8 ring structures or macrocyclic rings (C8 or higher). Cyclic compounds can be monocyclic or fused polycyclic compounds. Other cyclic compounds can be heterocyclic compounds (e.g., rings having at least oxygen or nitrogen atoms) having two or more vinyl substituents. One example of a vinyl-substituted cyclic compound is divinylbenzene. Divinylbenzene can be provided by Sigma-Aldrich.
[0091] In other embodiments, the coupling agent can include vinyl substituted low molecular weight silicones or combinations thereof with other coupling agents disclosed herein. Low molecular weight silicones have molecular weights (M) of less than 1000, 750, 600, 500, 450, 400, or 350 g / mol. wThe low molecular weight silicone may be substituted with two or more vinyl groups, for example, three, four or more vinyl groups. In one example, the vinyl groups may be substituted on the Si atom of the silicone compound.
[0092] In other embodiments, the coupling agent may be a cyclic compound substituted with two or more alkyl groups. The alkyl groups may include alkyls having 1-20 carbon atoms. The alkyl groups may be linear or branched, for example, di- and tri-alkyl groups. The cyclic compounds may include C3-C8 ring structures or macrocyclic rings (C8 or higher). The cyclic compounds may be monocyclic or fused polycyclic compounds. Other cyclic compounds may be heterocyclic compounds (e.g., rings having at least an oxygen or nitrogen atom) with two or more vinyl substituents. Examples of cyclic compounds substituted with alkyl groups include 1,3-diisopropylbenzene and 1,4-diisopropylbenzene.
[0093] Adhesion testing of the treated aramid fibers described herein may be performed to provide a quantitative measurement of adhesion between the fiber and the matrix. An example of a preferred adhesion test is shown in Example 4 below, and a schematic of the adhesion test is shown in Figures 7 and 8. The adhesion test involves optionally twisting the aramid fibers, for example at 150 revolutions per meter, before embedding the fibers in the elastomeric material. The fibers are sandwiched between two materials and heated to cure the material and bond it to the fiber. For example, the uncured material and fiber may be placed in a melt press and heated for a period of time, for example, 5 minutes to 1 hour, 10 to 50 minutes, or 20, 30, or 40 minutes. Heating to a curing or bonding temperature may include raising the material temperature to a temperature in the range of 50 to 250°C, 75 to 200°C, or up to 100, 125, 150, 160, 170, 180, or 190°C.
[0094] The aramid fibers embedded in the elastomeric material are cut to provide a test sample having one or more aramid fibers extending outward from the block of elastomeric material, and the one or more aramid fibers or bundles are then pulled until they break, i.e., the fibers are pulled completely out of the elastomeric material.
[0095] A basic shear lag model is used to calculate the adhesion between the fiber and the elastomeric material. The model assumes that the increase in tensile stress along the fiber length is entirely due to shear forces acting at the cylindrical interface between the fiber and the elastomeric material. Considering the differential elements shown in Figure 8 and balancing the forces, we obtain Eq. (1).
number
[0096] Assuming that the stress is constant over the length of a fiber embedded in an elastomeric material, the shear stress (Pa or N / m 2 ) (i.e., an index of adhesion) can be calculated by equation (2).
number
[0097] where (F) is tension in Newtons (N), D is the diameter of the fiber or fiber bundle (meters), and L is the displacement (meters) through the elastomeric material.
[0098] As shown in the examples herein, one or more treatment methods can be applied to aramid fibers to improve the adhesion of the fibers to elastomeric materials. The treated aramid fibers can be used in a variety of applications where such improved adhesion is beneficial. For example, the aramid fibers can be used in rubber products such as tires (e.g., belt plies, body plies, beads, reinforcing members), belts (e.g., conveyors), and reinforced air springs. The treated aramid fibers can be combined with vulcanizable compositions. For example, the fibers can be embedded in the composition as reinforcing members.
[0099] The vulcanizable rubber composition can be prepared by forming an initial masterbatch that includes the rubber component and the filler. The mixing of this initial masterbatch can be performed at an initiation temperature of about 25°C to about 125°C and an extrusion temperature of about 135°C to about 180°C. To prevent premature vulcanization (also known as scorch), the initial masterbatch can be free of any vulcanizing agents. Once the initial masterbatch is processed, in a final mix stage, vulcanizing agents can be introduced and mixed into the initial masterbatch at a lower temperature. At this stage, the vulcanization process cannot begin. Optionally, an additional mix stage, often called a remill, can be used between the masterbatch mix stage and the final mix stage. The treated aramid fibers can be combined with the uncured composition. For example, the fibers can be extruded with the composition or sandwiched between layers of uncured material. Rubber compounding techniques and additives used therein are generally known, as disclosed in The Compounding and Vulcanization of Rubber, in Rubber Technology (2nd Ed. 1973). Applicable mixing conditions and procedures for silica-filled tire compounds are known, as described in U.S. Pat. Nos. 5,227,425, 5,719,207, 5,717,022, and European Patent No. 890,606, all of which are incorporated herein by reference. EXAMPLES
[0100] The following examples are illustrative of specific and representative embodiments and / or features of the embodiments of the present disclosure. The examples are provided for illustrative purposes only and should not be construed as limiting the present disclosure. Many modifications to these specific examples are possible without departing from the spirit and scope of the embodiments of the present disclosure. More specifically, the specific rubbers, fillers and other ingredients (e.g., antioxidants, curing agents, etc.) used in the examples should not be construed as limiting, since other ingredients may be substituted as disclosed in the detailed description. That is, the specific ingredients in the composition and their respective amounts and relative amounts should be understood to apply to the general content of the detailed description.
[0101] Example 1 Acid treatment of Kevlar fabric
[0102] Kevlar fibers were obtained from DuPont. The fibers were observed using a scanning electron microscope. An image of the fibers is shown in Figure 1.
[0103] A portion of the Kevlar fiber was immersed in a 12M solution of HCl and another portion of the Kevlar fiber was immersed in a 12M solution of sulfuric acid (H2SO4). The immersion period was 24 hours. The immersed fibers were observed using a scanning electron microscope. Images of the fibers immersed in HCl and H2SO4 are shown in Figures 2 and 3, respectively. As shown, the fiber surface was modified and showed roughness and holes, which imparted surface roughness to the fibers.
[0104] Example 2 Microwave / acid treatment of Kevlar fabric.
[0105] Kevlar fibers obtained from DuPont were immersed in a 50 wt% aqueous sulfuric acid solution for 1 hour. The fibers were removed from the sulfuric acid solution and immersed in deionized water. The immersed fibers were then irradiated with microwaves at 100 watts power for 2 minutes. The fibers were removed from the water and allowed to dry. The dried fibers were observed using a scanning electron microscope. Images of the fibers are shown in Figures 3 and 4. As shown, the fiber surface was modified and exhibited blister morphology. This may be the result of acid remaining within the voids or porous surface of the fiber attempting to escape through the fiber surface upon exposure to microwave energy.
[0106] Example 3 Mechanical treatment of Kevlar fibers
[0107] Kevlar fibers obtained from DuPont were passed through a curved surface of 2 mm diameter at a speed of 500 mm / min and a load of 1 N using an Instron tensile tester. The device used to apply uniform and uniform compressive and bending strain to the fiber is shown in Figure 5. The fiber was bent at an angle of 120° around the curved surface. The mechanically treated fibers were embedded in a transparent polystyrene matrix and observed under an optical microscope. An image of the mechanically treated fiber is shown in Figure 6.
[0108] The fibers exhibited "V" shaped notches or kink bands suggesting buckling at the fiber surface. Tests performed on the fibers indicate that they deform non-Hookean at small bending strains, suggesting that the deformation is plastic in nature. The modified surface of the fibers indicates that mechanical treatment of the fibers to impart bending strains is an efficient and effective method of introducing roughness into the fiber surface.
[0109] Example 4 Adhesion testing of untreated and treated fibers
[0110] Kevlar fibers obtained from DuPont were divided into batches for testing adhesion to rubber compositions, the rubber compositions used being set forth in Table 1 below.
[0111] [Table 1]
[0112] A first portion of the fibers was tested without treating the fibers prior to adhering to the rubber composition (i.e., "untreated"). A second portion of the fibers was immersed in divinylbenzene and a third portion of the fibers was immersed in divinylbenzene with a molecular weight (M w The second and third portions of the fibers were soaked for 1 hour at 25° C. The fourth and fifth portions of the fibers were soaked in the presence of supercritical carbon dioxide with divinylbenzene and a low molecular weight silicone having a molecular weight (M) of about 345 g / mol, respectively. w The material was immersed in a vinyl substituted low molecular weight silicone having a carboxylic acid of 1,2-dichloro-1,2-diphenyl-2,4-tetrafluoroethylene (CO) content of 1,2-dichloro-1,2-diphenyl-2,4-diphenyl-2,5-tetrafluoroethylene (CO) content of 1,2-dichloro-1,2-diphenyl-2,5-tetrafluoroethylene (CO) content of 1,2-diphenyl-2,4-diphenyl-2,
[0113] Adhesion specimens were prepared and tested for five sets of fibers. The adhesion test is referred to herein as Test #1, as described below. This test was used to measure and generate adhesion data in the Examples below. Adhesion tests were performed using an Instron tensile tester. After processing, a fixed amount of twist of 150 revolutions per meter was applied to the fibers. The fibers were then placed between two strips of the rubber composition shown in Table 1 above. Studies have shown that twisting the fibers has the effect of projecting a uniform and consistent surface area into the matrix, which can reduce dispersion of adhesion data. A schematic of the adhesion test specimen preparation is shown in FIG. 7. And the shear lag model of the adhesion test to measure the adhesion of the fiber to the rubber matrix is shown in FIG. 8.
[0114] The adhesion results measured for untreated and treated fibers (5 sets) are shown in FIG. 9. The fibers soaked in divinylbenzene and low molecular weight silicone showed higher adhesion to the rubber composition compared to the untreated fibers. The fibers soaked in divinylbenzene at ambient conditions showed adhesion greater than 1 MPa and about 1.1 MPa. The fibers soaked in low molecular weight silicone at ambient conditions showed adhesion greater than 1 MPa and about 1.03 MPa. The fibers soaked in divinylbenzene in the presence of supercritical carbon dioxide showed adhesion greater than 0.9 MPa and about 0.97 MPa. The fibers soaked in low molecular weight silicone in the presence of supercritical carbon dioxide showed adhesion greater than 0.8 MPa and about 0.87 MPa. As shown, all treated fibers showed adhesion greater than 0.8 MPa and about 0.85 MPa. This is a significant improvement compared to the adhesion results of the untreated fibers, which showed adhesion of about 0.57 MPa.
[0115] Example 5 Adhesion testing of untreated and treated fibers
[0116] Kevlar fibers obtained from DuPont were split into batches for adhesion testing to rubber compositions as described in Example 4 above.
[0117] A first portion of the fibers was tested without treating the fibers prior to bonding to the rubber composition (i.e., "untreated"). A second portion of the fibers was immersed in a 50 wt. % aqueous sulfuric acid solution for 1 hour, removed from the acid solution, and further immersed in divinylbenzene in a high pressure vessel at 5,000 psi and 50° C. in the presence of supercritical carbon dioxide for 1 hour. A third portion of the fibers was not acid treated and was immersed in divinylbenzene in a high pressure vessel at 5,000 psi and 50° C. in the presence of supercritical carbon dioxide for 1 hour.
[0118] The adhesion results measured for the untreated and treated fibers (3 sets) are shown in FIG. 10. The fibers immersed in sulfuric acid and then immersed in divinylbenzene in the presence of supercritical carbon dioxide showed adhesions of 0.9 MPa and greater than about 0.99 MPa. The fibers immersed in divinylbenzene in the presence of supercritical carbon dioxide without acid treatment showed adhesions of 0.9 MPa and greater than about 0.97 MPa. As shown, all treated fibers showed adhesions of 0.9 MPa and greater than 0.95 MPa. This is a significant improvement over the adhesion results for the untreated fibers, which showed an adhesion of about 0.57 MPa.
[0119] Example 6 Adhesion testing of untreated and treated fibers
[0120] Kevlar fibers obtained from DuPont were split into batches for adhesion testing to rubber compositions as described in Example 4 above.
[0121] A first portion of the fiber was tested without treating the fiber prior to bonding to the rubber composition (i.e., "untreated"). A second portion of the fiber was immersed in a 50 wt % aqueous sulfuric acid solution for 1 hour, removed from the acid solution, and dried. The immersed fiber was then irradiated with microwaves at 100 watts for 2 minutes. The fiber was removed from the water and immersed in divinylbenzene at 25° C. for 1 hour. The molecular weight (M) of about 345 g / mol was determined. w A third portion of the fibers was treated similarly to the second portion, except that a low molecular weight silicone having a molecular weight (M) of about 345 g / mol was used instead of divinylbenzene. A fourth portion of the fibers was treated similarly to the second portion, except that divinylbenzene was used in a high pressure vessel at a pressure of 5,000 psi and a temperature of 50° C. for 1 hour in the presence of supercritical carbon dioxide to apply the coupling agent. w A fifth portion of the fibers was treated similarly to the fourth portion, except that a low molecular weight silicone having a .alpha.-dimethylsiloxane moiety was used instead of divinylbenzene.
[0122] The adhesion results measured for untreated and treated fibers (5 sets) are shown in FIG. 11. The second section of the fiber showed adhesion greater than 0.5 MPa and 0.53 MPa, the third section showed adhesion greater than 0.8 and 0.81 MPa, the fourth section showed adhesion greater than 1.05 and 1.1 MPa, and the fifth section showed adhesion greater than 0.8 and 0.89 MPa. As shown, the presence of supercritical carbon dioxide improved the adhesion results compared to fibers immersed in coupling agent at ambient conditions. It is believed that the blister morphology of the fiber surface may be caused by residual acid trying to escape voids under the fiber surface. This surface morphology may have allowed the supercritical carbon dioxide to have better access under the surface.
[0123] Example 7 Adhesion testing of untreated and treated fibers
[0124] Kevlar fibers obtained from DuPont were split into batches for adhesion testing to rubber compositions as described in Example 4 above.
[0125] A first portion of the fibers was tested without treating the fibers prior to bonding to the rubber composition (i.e., "untreated"). A second portion of the fibers was mechanically treated as described in Example 3 and then immersed in divinylbenzene for 1 hour in the presence of supercritical carbon dioxide at a pressure of 5,000 psi and a temperature of 50°C. A third portion of the fibers was mechanically treated as described in Example 3 and then the fibers were immersed in divinylbenzene for 1 hour in the presence of supercritical carbon dioxide at a pressure of 5,000 psi and a temperature of 50°C. w ) in a high pressure vessel at a pressure of 5,000 psi and a temperature of 50° C. for 1 hour.
[0126] The adhesion results measured for the untreated and treated fibers (3 sets) are shown in Figure 12. The second section of fibers that were mechanically treated and dipped in divinylbenzene showed adhesions of 1.15 and greater than about 1.17 MPa. The third section of fibers that were mechanically treated and dipped in low molecular weight silicone showed adhesions of 1.1 and greater than about 1.15 MPa. As shown, all treated fibers showed adhesions of 1 MPa and greater than 1.1 MPa. This is a significant improvement over the adhesion results for the untreated fibers, which showed an adhesion of about 0.57 MPa.
[0127] All references, including but not limited to patents, patent applications, and non-patent literature, are incorporated herein by reference in their entirety.
[0128] While various aspects and embodiments of the compositions and methods are disclosed herein, other aspects and embodiments will be apparent to those of ordinary skill in the art. The various aspects and embodiments disclosed herein are for illustrative purposes only and are not intended to limit the true scope and spirit of the appended claims.
Claims
1. 1. A method for improving adhesion of aramid fibers to an elastomeric material, comprising the steps of: (a). contacting aramid fibers with a coupling agent fluid; (b) removing aramid fibers from the fluid; (c) drying the aramid fibers; The method wherein the coupling agent is a divinyl-substituted cyclic compound or a low molecular weight vinyl-substituted silicone having a molecular weight (Mw) of less than 1000.
2. The method of claim 1 , wherein the aramid fibers are poly(paraphenylene terephthalamide) or poly(metaphenylene isophthalamide).
3. The method of claim 1 , wherein the coupling agent fluid of step (a) is a coupling agent mixed with a solvent.
4. The method of claim 3 , wherein the solvent is an organic solvent.
5. The method of claim 3 , wherein the solvent is supercritical carbon dioxide.
6. The aramid fibers have an adhesion to a rubber composition of greater than 0.8 MPa; 2. The method of claim 1, wherein the adhesion is from an adhesion test conducted using an Instron tensile tester in which the aramid fibers are twisted at a fixed amount of 150 revolutions per meter and then the aramid fibers are placed between two strips of the following rubber composition: <Rubber Composition> A rubber composition consisting of 100 phr natural rubber, 65 phr carbon black, 10 phr naphthenic oil, 1.3 phr stearic acid, 5 phr zinc oxide, 1.2 phr sulfur, 0.8 phr N-tert-butylbenzothiazole-2-sulfonamide (TBBS), and 1.3 phr 2,2'-dithiobisbenzothiazole (MBTS).
7. 10. The method of claim 1, wherein prior to step (a), the aramid fibers are contacted with an acid solution.
8. 10. The method of claim 1, wherein prior to step (a), the aramid fibers are irradiated in a liquid.
9. 2. The method of claim 1, wherein prior to step (a), the aramid fibers are bent at an angle greater than 30 degrees while a constant tension is applied to the aramid fibers.
10. The method of claim 1 , wherein the aramid fibers are aramid fibers that have been in contact with a coupling agent fluid for at least 30 minutes.
11. The method of claim 1, wherein the divinyl-substituted cyclic compound is divinylbenzene.
Citation Information
Patent Citations
Method of surface-treatment for aramid fiber and surface-treated fiber
JP2001303456A
Poly-para-phenylene terephthalamide fiber and method for producing the same fiber and its use
JP2007297722A